Evaluation of the Modified Barium Swallow Study Conducted With and Without Radiologist Supervision: A Pre- and Post-Observational Study. Issue 1 (February 2022) - Yang, Luhe; Leswick, David; Butler, Michael; Ellchuk, Tasha
Purpose: Assess quality metrics of modified barium swallow studies (MBSS) with and without a radiologist present during the procedure. Methods: Retrospective review of MBSS performed on adult inpatients at a tertiary care hospital 6-months pre- and post-institutional change from having to not having a radiologist present during the examination. Factors assessed included: fluoroscopy time; study duration; number of cine loops; number of images; efficiency of collimation (using a 5-point scoring system); time to final report; radiologist-speech language pathologist report disagreement; and recalls for inadequate studies. Statistical analysis was via Welch's t-test and a test of proportions for continuous and count data under the normal approximation. Results: 106 and 119 MBSS were analyzed from the radiologist present and radiologist absent periods, respectively. No statistically significant differences were found for: average fluoroscopy time (116.1 s vs. 126.9 s; P = 0.161); study duration (400.4 s vs. 417.3 s; P = 0.453); number of cine loops (9.3 vs. 10.2; P = 0.075); number of images (620.5 vs. 581.1; P = 0.350); or report disagreement. There was improved performance without the radiologist present for collimation (1.92 vs. 1.43; P = 0.003) and fewer non-diagnostic images (6.5 vs. 4.5; P = 0.001). Time to final report was longer with the radiologist absent due to more reports with significant delays. There were no repeated studies because of inadequate technique in either group. Conclusion: MBSS performed by technologists without radiologist supervision is not inferior to those performed with radiologist supervision on multiple performance measures. This supports technologist operated MBSS without radiologist supervision, while acknowledging a need to further address radiologist report time delay.